Manejo de fracturas tibiales, grado 3c, en el primer nivel de atención de salud - Paredes Farez, Allison Mishel (Machala : Universidad Técnica de Machala, 2024)
INTRODUCTION: Open fractures, especially grade III C fractures of the tibia, represent a significant challenge in the field of traumatology due to their complexity and high rate of complications. These injuries result from high-energy trauma, such as traffic accidents, and are characterized by exposure of the bone to the external environment through a skin and soft tissue wound. Associated complications include infections, compartment syndrome, no bone junction, and, in severe cases, amputations. OBJECTIVE: To describe the management of tibial fractures, grade III C, in primary health care. METHODOLOGY: An exhaustive review of the available scientific literature on the management of exposed fractures of the tibia in databases such as Cocrhane, Scielo, Pubmed, from 2019 to 2024. DEVELOPMENT: Open fractures of the tibia, especially grade III C, require a multidisciplinary approach and multiple surgical interventions. The infection rate in these fractures varies significantly, between 3% and 40%, depending on factors such as the type of fracture, the degree of injury in soft tissues and the treatment strategies implemented. The modern management of these fractures focuses on three fundamental pillars: prevention of infections, early stabilization of fracture and adequate coverage of soft tissues. CONCLUSION: The complexity of grade 3C open tibial fractures requires multidisciplinary management that includes the administration of broad-spectrum antibiotics and timely referral to centers with greater resolution capacity.
INTRODUCCIÓN: Las fracturas abiertas, especialmente las de grado III C de la tibia, representan un reto significativo en el ámbito de la traumatología debido a su complejidad y alta tasa de complicaciones. Estas lesiones resultan de traumatismos de alta energía, como accidentes de tráfico, y se caracterizan por la exposición del hueso al medio externo a través de una herida en la piel y los tejidos blandos. Las complicaciones asociadas incluyen infecciones, síndrome compartimental, no unión ósea y, en casos severos, amputaciones. OBJETIVO: Describir el manejo de las fracturas tibiales, grado III C, en atención primaria de la salud. METODOLOGÍA: Revisión exhaustiva de la literatura científica disponible, sobre el manejo de fracturas expuestas de tibia, en bases de datos como Cocrhane, Scielo, Pubmed, desde el 2019 al 2024. DESARROLLO: Las fracturas abiertas de tibia, especialmente las de grado III C, requieren un abordaje multidisciplinario y múltiples intervenciones quirúrgicas. La tasa de infección en estas fracturas varía significativamente, entre el 3% y el 40%, dependiendo de factores como el tipo de fractura, el grado de lesión en los tejidos blandos y las estrategias de tratamiento implementadas. El manejo moderno de estas fracturas se centra en tres pilares fundamentales: la prevención de infecciones, la estabilización temprana de la fractura y la cobertura adecuada de los tejidos blandos. CONCLUSIÓN: La complejidad de las fracturas tibiales abiertas grado 3C requiere de un manejo multidisciplinario que incluya la administración de antibióticos de amplio espectro y la referencia oportuna a centros de mayor capacidad resolutiva.
Keywords: TIBIA; FRACTURAS EXPUESTAS; GRADO IIIC; DIAGNOSTICO